The Role of Public Relations in Reducing the Negative Phenomena of Social Media site: Conference on Cultural Diversity, the Basis of National Integration, College of Arts/Wasit University 2022 - Feras Esmeal Khamees, Lecture: (lark, 2022)
The Internet provides many applications and features, such as communication, access and dissemination of information, but some ill-intentioned and Mean- Spirited individuals have chosen to use these features to commit unlawful acts, infringe on the rights of others, such as spreading hatred and racism, content contrary to public morals and decency, defaming others, violating their right to private life and other. And if the crimes in the world The real Restricted - sometimes - against to unknown, and Stops at here, which means the loss of the rights of the compensation for the harm they have suffered, but his does not represent a large percentage and the matter is different in internet area, and therefore we can not only play a negative role, but must look for a way to enable the affected to compensation, Right of reputation is one of the highest rights to be protected, which is a fundamental component of the concern of most Constitutions and laws is To protect the human right of reputation, and the role of public relations is to correct what is wrong and work to improve the image or re-correct misinformation